1967
DOI: 10.1002/j.2164-4918.1967.tb04555.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Orientation of College Students' Wives

Abstract: 52 per cent of a selected sample of wives of Texas Technological College students responded to a questionnaire that furnished a description of their education, their employment and family status as well as indications of their attitudes toward higher education and possible college courses in which they might enroll if interested. Results show the average wife of a student is between 20 and 24 years of age, is employed, has one preschool child. A college education is more important to the majority “now” than it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1976
1976
1976
1976

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hildebrand [9] indicated that a college education was viewed as more important to student wives during the couples' years on campus than when the wives first married.…”
mentioning
confidence: 99%
“…Hildebrand [9] indicated that a college education was viewed as more important to student wives during the couples' years on campus than when the wives first married.…”
mentioning
confidence: 99%